1989
DOI: 10.1063/1.342635
|View full text |Cite
|
Sign up to set email alerts
|

On the role of oxygen and hydrogen in diamond-forming discharges

Abstract: Plasma emission actinometry has been used to study the mechanism by which small additions of oxygen (∼0.5%) enhance the rate of diamond deposition in a dilute (4%) CH4/H2 discharge at high temperature (900–1300 K). Increasing amounts of CH4 in the feed depress [H], while increasing the O2 concentration, up to ∼5%, produces a fivefold increase in atomic hydrogen in the discharge zone. Invoking a mechanism where diamond growth competes with the formation of an amorphous/graphitic inhibiting layer, these results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(54 citation statements)
references
References 24 publications
2
51
1
Order By: Relevance
“…In addition, we detect excited H 2 from the Fulcher-a band system B600 nm ( Supplementary Fig. S3b) 20 . The confirmation of C 2 and CH radicals is particularly important for nanodiamond formation.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, we detect excited H 2 from the Fulcher-a band system B600 nm ( Supplementary Fig. S3b) 20 . The confirmation of C 2 and CH radicals is particularly important for nanodiamond formation.…”
Section: Resultsmentioning
confidence: 92%
“…The confirmation of C 2 and CH radicals is particularly important for nanodiamond formation. Previous reports have shown that C 2 species initially nucleate a solid carbon cluster, and CH species form a hydrocarbon layer, promoting the nucleation of nanodiamonds 20,21 ; however, these experiments were carried out on films where the substrate may also influence nucleation 22,23 . The addition of H 2 gas results in a new feature in the OES spectra at 656 nm corresponding to the H a Balmer line (see right panel of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported enhanced growth rates or quality due to oxygen addition and, more importantly, the substrate temperature can be significantly lowered when oxygen is introduced into the hydrocarbon/H 2 gas mixtures [73][74][75][76][77][78].…”
Section: Effect Of Oxygen Additionmentioning
confidence: 99%
“…In the PE-CVD of diamond films, oxygen is added to a CH 4 /H 2 system to obtain a high growth rate and/or an improvement of the quality of the resultant films [35][36][37][38]. Several authors have discussed the role of oxygen in diamond growth.…”
Section: Article In Pressmentioning
confidence: 99%
“…Several authors have discussed the role of oxygen in diamond growth. Mucha et al [37] pointed out that the addition of oxygen to a CH 4 /H 2 system increases the concentration of atomic hydrogen; correspondingly, the formation of amorphous and graphitic carbon, which would otherwise inhibit diamond growth, is suppressed. From a detailed chemical kinetics model that describes both gas phase and surface processes occurring in diamond CVD, Frenklach and Wang [38] postulated that OH radicals and atomic oxygen gasify sp 2 carbon and suppress the formation of aromatic species in the gas phase.…”
Section: Article In Pressmentioning
confidence: 99%